Rising political populism and outmigration of youth as international students - Murat Demirci (Koç University-TÜSIAD Economic Research Forum (ERF), 2021)
Populism is on the rise, and democratic rights are deteriorating in many countries as a result of authoritarian policies adopted by populist leaders. This study analyzes how rising political populism in developing countries affects whether their citizens pursue higher education abroad. Applying the Synthetic Control Method, student migration patterns from Hungary, Ukraine, Venezuela, and Indonesia are explored as cases constituting early examples of populism. The estimates show that the rise of populism in these countries increases the number of citizens who attend universities in foreign countries. Limited evidence for worsening higher education options in the origin countries suggests that more students start pursuing foreign education to increase their chances of living abroad after graduation.
Keywords: F22; I23; J24; O15; 330; International Students; Outmigration of Skilled People; Political Populism; Synthetic Control Method